Homeodomain-only protein suppresses proliferation and contributes to differentiation- and age-related reduced CD8+ T cell expansion - Yang, Qian; Patrick, Michael; Lu, Jian; Chen, Joseph; Zhang, Yongqing; Hemani, Humza; Lehrmann, Elin; De, Supriyo; Weng, Nan-ping (Frontiers in Immunology, 2024)
T cell activation is a tightly controlled process involving both positive and negative regulators.The precise mechanisms governing the negative regulators in T cell proliferation remain incompletely understood. Here, we report that homeodomain-only protein (HOPX), a homeodomain-containing protein, and its most abundant isoform HOPXb, negatively regulate activation-induced proliferation of human T cells. We found that HOPX expression progressively increased from naïve (TN) to central memory (TCM) to effector memory (TEM) cells, with a notable upregulation following in vitro stimulation. Overexpression of HOPXb leads to a reduction in TN cell proliferation while HOPX knockdown promotes proliferation of TN and TEM cells. Furthermore, we demonstrated that HOPX binds to promoters and exerts repressive effects on the expression of MYC and NR4A1, two positive regulators known to promote T cell proliferation. Importantly, our findings suggest aging is associated with increased HOPX expression, and that knockdown of HOPX enhances the proliferation of CD8 + T cells in older adults. Our findings provide compelling evidence that HOPX serves as a negative regulator of T cell activation and plays a pivotal role in T cell differentiation and in age-related-reduction in T cell proliferation.Elevated expression of HOPX following engagement of TCR and co-stimulatory receptors leads to the suppression of activation-induced proliferation in human T cells, while leaving cell survival unaffected. The increased HOPX expression is linked to reduced proliferation in vitro from TN to memory cell differentiation (TCM and TEM) and in the context of aging. HOPX exerts its suppressive influence by directly inhibiting the transcription of two pivotal genes associated with proliferation and TCR signaling, namely MYC and NR4A1. These findings reveal a novel mechanism for the negative regulation of T cell proliferation following activation.